A comprehensive review on the processing of dried fish and the associated chemical and nutritional changes - Fitri, Nursyah; Xi, Sharon Ying Chan; Che Lah, Noor Hanini; Jam, Faidruz Azura; Mohmad Misnan, Norazlan; Kamal, Nurkhalida; Sarian, Murni Nazira; Mohd Lazaldin, Mohd Aizuddin; Chen, Fei Low; Hamezah, Hamizah Shahirah; Rohani, Emelda Rosseleena; Mediani, Ahmed; et al. (MDPI, 2022)
Fish is a good source of nutrients, although it is easily spoiled. As such, drying is a common method of preserving fish to compensate for its perishability. Dried fish exists in different cultures with varying types of fish used and drying methods. These delicacies are not only consumed for their convenience and for their health benefits, as discussed in this review. Most commonly, salt and spices are added to dried fish to enhance the flavours and to decrease the water activity (aw) of the fish, which further aids the drying process. For fish to be dried effectively, the temperature, drying environment, and time need to be considered along with the butchering method used on the raw fish prior to drying. Considering the various contributing factors, several physicochemical and biochemical changes will certainly occur in the fish. In this review, the pH, water activity (aw), lipid oxidation, and colour changes in fish drying are discussed as well as the proximate composition of dried fish. With these characteristic changes in dried fish, the sensory, microbial and safety aspects of dried fish are also affected, revolving around the preferences of consumers and their health concerns, especially based on how drying is efficient in eliminating/reducing harmful microbes from the fish. Interestingly, several studies have focused on upscaling the efficiency of dried fish production to generate a safer line of dried fish products with less effort and time. An exploratory approach of the published literature was conducted to achieve the purpose of this review. This evaluation gathers important information from all available library databases from 1990 to 2022. In general, this review will benefit the fishery and food industry by enabling them to enhance the efficiency and safety of fish drying, hence minimising food waste without compromising the quality and nutritional values of dried fish.